Antibiotic profile in pediatric wards, Department of Child Health, Cipto Mangunkusumo Hospital - Amin Husni; Hardjono Abdoerrachman; Arwin Akib (Indonesian Pediatric Society, 2004)
Introduction The medical profession has currently come to a con-clusion that the major problem in the future is failure of treatmentdue to antibiotic-resistant microorganisms.Objective The aim of this study was to determine the profile ofantibiotics used in the Pediatric Wards of Department of Child Health,Medical School, University of Indonesia, Cipto Mangunkusumo Hos-pital, Jakarta.Methods A descriptive retrospective study was conducted on all pa-tients hospitalized in the Pediatric Wards of Department of Child Health,Medical School, University of Indonesia, Cipto Mangunkusumo Hos-pital during June–July 2001. Data were obtained from the medicalrecords of the patients.Results Three hundreds and fifty-six hospitalized patients fulfilledthe inclusion criteria. The antibiotics were given to 48.7% of thepatients. The greatest user of antibiotics was the age group of 1-5year-old, 50% of patients had been given single antibiotic and therest given combined antibiotics. The ICU used antibiotics most fre-quently in contrast to the one-day care unit which used least. Thegreatest use of single antibiotic was in the class 1-2 wards whilecombined antibiotics were mostly used in the third class wards.Single antibiotics used were cefotaxime (49.4%), amoxicillin(20.7%), and ampicillin (11.55%). Combined antibiotics used wereampicillin + chloramphenicol (34.5%), cotrimoxazole (21.8%),cefotaxime + amikacin (5.7%), cefotaxime + cotrimoxazole (5.7%),and cefotaxime + isoniazid + rifampicin + pyrazinamide (5.7%).Conclusions The antibiotics most commonly used singly wascefotaxime. The combination of antibiotic mostly used was ampi-cillin + chloramphenicol